Pengembangan Asesmen Hots Multiple Choice Mengunakan Aplikasi Quizizz Di Sekolah Dasar - Dicky Dermawan, Deden; Arrahim (Elementary Teacher Education Program, Majalengka University, 2023)
Research on developing assessments based on Higher Order Thinking Skills (HOTS) with the help of the quizizz application during learning from home by utilizing features in online applications in the learning process. This study aims to produce a Higher Order Thinking Skill (HOTS) based assessment for fifth grade elementary schools in science learning theme 8 The environment of our friend that is valid, reliable, feasible, and practical. This research method uses R&D research with the ADDIE research design (analysis, design, development, implementation, and evaluation). The steps developed include design, expert validation, limited scale trials, and large scale trials. The assessment developed is a multiple choice question using the quizizz application. Data collection techniques in this development research using test techniques (multiple choice) and practicality questionnaires. The results of the HOTS-based multiple choice assessment validation are valid, the reliability value when the limited scale trial is 0.648 and when the large scale trial is 0.762 the value indicates the assessment is reliable. revisions